(untitled) (Fiep Bulletin - online, 2013)
This study aimed to implement a program of gymnastics within two units of a higher education institution (UNIP-SP), benefiting employees of the cleaning sector to improve activity of daily living (ADLs), quality of work life and preventing occupational injuries. The study was conducted between the periods from August to December 2011. We selected 20 subjects in total being 12 unit Marquis (Neighborhood Water White-SP) and 8 unit Alphaville (City of Santana de Parnaíba-SP). All subjects signed an Informed Consent Form and Receipt clarifica ¬ guaranteeing the anonymity and the possibility of withdrawal. Were used for the initial diagnosis three assessment tools: (1) Questionnaire topography and intensity of pain, (2) stress level test comprised 18 closed questions, with scales of zero to five and, (3) Evaluation Questionnaire quality of life and health (QVS-80) composed of 80 closed questions permeating personal information, lifestyle and health, physical activity in the company, the work environment and quality of life. The data contained in the application forms were entered and tabulated using Microsoft Office Excel 2007. Only six items most emerging were studied: pain, discomfort during working hours, sleep, stress levels, illness and activities of daily living (ADL), the 30 graphs tabulated. Initially it was applied to a preparatory Gymnastics period of 120 days being held twice a week lasting 10 to 15 minutes of class. After this period was applied again diagnosis, seeking positive changes. The results showed a reduction of 26% and 21% in body pain, improvement in quality of sleep and stress reduction, proving the importance of the permanence of physical activity within the work environment through Gymnastics.